Evaluation of different levels of potassium on the yield and protein content of wheat in the high Ganges river floodplain soil (Bangladesh Journal of Agricultural Research, 2010)
Balanced fertilization with optimum potassium management may lead to maximize wheat yield. The experiment was carried out at the Farming Systems Research and Development (FSRD site, Pushpapara, Pabna during the rabi seasons of 2003-04 and 2004-05 to ascertain the effect of potassium application on wheat. Five different levels of potassium (K) were tested on wheat crop. Yield contributing characters and yield exerted significant variation due to application of different levels of K and the best performance of the crop parameters was recorded when 36 kg K/ha was applied. Remarkable increase in grain, straw and total biomass yield was recorded in the same treatment. Regarding the grain quality of wheat, the highest protein content was recorded from 36 kg K/ha, which was 6.86% and 4.98% higher over omission of K (control) and recommended dose (100% estimated K). The highest net benefit was obtained from 36 kg K/ha, which was 40.52% higher over omission of K (control). Key Words: Potassium; yield; protein content; wheat. DOI: 10.3329/bjar.v34i1.5759Bangladesh J. Agril. Res. 34(1) : 97-104, March 2009